A Contextualized Groundwater Governance Framework for Sarlahi, Nepal - Pokhrel, Ayushmita; KC, Saurav (International Journal on Engineering Technology, 2025)
Effective groundwater governance is vital for sustainable resource management. This study presents a contextualized groundwater governance assessment framework applied to Barahathawa Municipality, Sarlahi, Nepal. The framework evaluates governance across four dimensions—technical, legal/institutional, cross-sector policy coordination, and operational—using 32 indicators to derive a composite Groundwater Governance Index (GGI). Barahathawa’s GGI of 1.03 reflects an early acceptable governance state. The technical dimension (midway between non-existent and basic) highlights gaps in groundwater data collection and dissemination. Legal and institutional mechanisms are approaching a basic level but are limited by the absence of comprehensive regulatory frameworks. Cross-sector policy coordination has reached an acceptable state, reflecting efforts to collaborate with local units/departments and sectoral entities, although these efforts are often informal and ad hoc. The operational dimension demonstrates initial progress toward an acceptable state, with advancements in transparency, conflict resolution, and community engagement in groundwater management discussions. However, further efforts are needed to enhance inclusivity and to establish a community-focused groundwater management action plan. This assessment framework thus provides a holistic and context-specific approach to identifying strengths and gaps in groundwater governance. By integrating insights from both experts and community stakeholders, it serves as an effective tool for understanding governance dynamics and guiding targeted improvements.